Contextualization Review of the Interpretation of the Verses of the Fathul Qulub Book at the IMM Sukoharjo Regeneration Program - Nirwana AN, Andri; Mustofa, Dedy; Akhyar, Sayed (South East Asia Regional Intellectual Forum of Qoran Hadith (SEARFIQH), 2023)
Abdullah Saeed introduced the concept of contextual findings, which he termed contextualization, by establishing a structured and systematic framework of values. This framework consists of four key steps: first, preliminary considerations; second, initiating completion; third, understanding the text's meaning; and fourth, connecting the text to the present context. In light of this, researchers delved into the awareness of contextualization, focusing on verses from the book Fathul Qulub, based on instructors in the IMM Sukoharjo cadre program. The purpose of this study was to discern a contextualized comprehension of the verses from the Fathul Qulub book within the IMM Sukoharjo cadre program. This research employed a qualitative approach, conducting field research. The participants were intermediate instructors within the IMM Sukoharjo cadre program, and the object of the study was to find verses in the Fathul Qulub book. The findings of the study revealed that instructors' interpretations of the Fathul Qulub book's verses did not align with Abdullah Saeed's contextual interpretation steps. Instead, instructors tended to directly proceed to the fourth step without completing the necessary preceding steps. This meant skipping the crucial step of linking the text's interpretation to the current context, specifically in terms of the cadre or organization. Even at this fourth step, the contextualization was not fully in line with Abdullah Saeed's theory.